CEO Pay Disparity and Firm Value - Esfahani, Sharif Shekarchizadeh (Journal of Accounting and Finance, 2022)
Prior studies have reported mixed results with regard to the effect of CEO pay disparity on firm value. While one stream of studies provides evidence that, based on tournament theory, a higher wage difference between CEOs and VPs positively affects firm value, other studies refer to the managerial power theory and show that the relationship is in fact negative. In this study, I investigate the roots of prior mixed findings to identify what the true effect is, if any. I conclude that the findings of prior studies have been biased due to 1) the existence of biased observations in the ExecuComp database, 2) incomplete research models, and 3) the choices of sample period. I replicate prior studies, properly adjust their models, and identify biased observations in their sample to analyze how CEO pay disparity can affect firm value. I find that firm value is positively affected by the difference between the salary of CEOs and that of their VPs, which could also justify one of the reasons behind the increase in CEO pay disparity in recent years.